The IL-1 Receptor Is Required to Maintain Neutrophil Viability and Function During Aspergillus fumigatus Airway Infection - Ralph, Benjamin AWR; Lehoux, Melanie; Ostapska, Hanna; Snarr, Brendan D.; Caffrey-Carr, Alayna K.; Fraser, Richard; Saleh, Maya; Obar, Joshua J.; Qureshi, Salman T.; Sheppard, Donald C. (Frontiers in Immunology, 2021)
Aspergillus fumigatus airway infections are associated with increased rates of hospitalizations and declining lung function in patients with chronic lung disease. While the pathogenesis of invasive A. fumigatus infections is well studied, little is known about the development and progression of airway infections. Previous studies have demonstrated a critical role for the IL-1 cytokines, IL-1α and IL-1β in enhancing pulmonary neutrophil recruitment during invasive aspergillosis. Here we use a mouse model of A. fumigatus airway infection to study the role of these IL-1 cytokines in immunocompetent mice. In the absence of IL-1 receptor signaling, mice exhibited reduced numbers of viable pulmonary neutrophils and increased levels of neutrophil apoptosis during fungal airway infection. Impaired neutrophil viability in these mice was associated with reduced pulmonary and systemic levels of G-CSF, and treatment with G-CSF restored both neutrophil viability and resistance to A. fumigatus airway infection. Taken together, these data demonstrate that IL-1 dependent G-CSF production plays a key role for host resistance to A. fumigatus airway infection through suppressing neutrophil apoptosis at the site of infection.